The Predicted Performance of Natural Ventilation Strategies in Islamic Boarding School Design in Magelang - Fenty Indarti; Iwan Indrawan; Fardilla Rizqiyah; Johanes Krisdianto; Nur Endah Nuffida; Ima Defiana (Pawon: Jurnal Arsitektur, 2023)
The importance issue in providing comfortable indoor air quality conflicts with the use of energy for mechanical cooling in tropics region such as Indonesia. Natural ventilation is seen as a potential to provide comfort through the change of air within the inside and outside of the space. Natural ventilation becomes a strategy to achieve building resilience towards climate change because it requires no energy consumption. Therefore, this research aims to justify the design of natural ventilation of low-income Islamic Boarding School in Magelang using steady state simulation. The results indicated that among three ventilation strategies simulated in this study, it can be concluded that stack effect is predicted to produce higher air flow rate which results to comfortable predicted observation on adaptive comfort.